Is There a Relationship between Ovarian Epithelial Dysplasia and Infertility?. (9th February 2012) - Chene, Gautier; Penault-Llorca, Frédérique; Tardieu, Anne; Cayre, Anne; Lagarde, Nicole; Jaffeux, Patricia; Aublet-Cuvelier, Bruno; Dechelotte, Pierre; Felloni, Bertrand; Pouly, Jean-Luc; Dauplat, Jacques
Abstract : Aim. Ovarian epithelial dysplasia was initially described in material from prophylactic oophorectomies performed in patients at genetic risk of ovarian cancer. Similar histopathological abnormalities have been revealed after ovulation stimulation. Since infertility is also a risk factor for ovarian neoplasia, the aim of this study was to study the relationship between infertility and ovarian dysplasia. Methods. We blindly reviewed 127 histopathological slides of adnexectomies or ovarian cystectomies according to three groups—an exposed group to ovulation induction ( n = 30), an infertile group without stimulation ( n = 35), and a spontaneously fertile control group ( n = 62)—in order to design an eleven histopathological criteria scoring system. Results. The ovarian dysplasia score was significantly higher in exposed group whereas dysplasia score was low in infertile and control groups (resp., 8.21 in exposed group, 3.69 for infertile patients, and 3.62 for the controls). In the subgroup with refractory infertility there was a trend towards a more severe dysplasia score (8.53 in ovulation induction group and 5.1 in infertile group). Conclusion. These results raise questions as to the responsibility of drugs used to induce ovulation and/or infertility itself in the genesis of ovarian epithelial dysplasia.